Antagonistic interaction between Fusarium oxysporum var. cumini and Aspergillus niger - Sameer Sharma (Journal of Research in Biology, 2012)
Antagonists are microorganisms that adversely affect another pathogen growing in association with it. Aspergillus niger have long been known as effective antagonists against plant pathogenic fungi and are the focus of much recent research. The antagonism between Aspergillus niger and Fusarium oxysporum var. cumini and the possible mechanism (s) of antagonism employed by Aspergillus niger when isolated from Capsicum annuum rhizosphere were investigated. Aspergillus niger was most effective, in causing significant suppression of growth and spore formation of Fusarium oxysporum var. cumini in plates and pots. Aspergillus niger was mycoparasitic on Fusarium oxysporum var. cumini and their hyphae grew over the hyphae of Fusarium oxysporum var. cumini. There was evidence that the mechanism of antagonism employed by Aspergillus niger were competition, lysis, penetration and hyperparasitism.